Clinical Outcomes From Cultivated Allogenic Stem Cells vs. Oral Mucosa Epithelial Transplants in Total Bilateral Stem Cells Deficiency - Samoila, Ovidiu; Gocan, Diana (Frontiers in Medicine, 2020)
Total bilateral limbal stem cell deficiency results from various pathologies, from burns (either chemical or physical) to Sjogren Syndrome, aniridia or ocular cicatricial pemphigoid. After the loss of stem cells, normal corneal epithelium is replaced by a more opaque and vascularized conjunctival epithelium, causing loss of vision. After 1997, cultivation techniques for limbal stem cells became possible. In parallel, cultivation techniques for oral mucosa epithelial cells were also available. The aim of our review was to summarize the clinical outcomes following allogenic cultured limbal stem cell transplant (allogenic CLET) and, on the other hand, oral mucosa derived epithelium transplant, (cultivated oral mucosa epithelial transplant – COMET or cultivated autologous oral mucosal epithelial cell sheet – CAOMECS), in the case of total bilateral limbal stem cell loss. 30 studies matching the inclusion criteria were found. The clinical improvement in both methods was reported similar, with percentages higher than 50% of the treated cases. However, the comparison between studies was difficult to achieve due to the lack of a universal and objective grading tool for assessing postoperative results. The definition of clinical improvement was problematic, because success was defined differently, depending on the study. Moreover, some of the studies followed both autologous and allogenic CLET, but described the results together, for both procedures, and therefore it was impossible to analyze them separately. COMET presented some advantages compared to CLET. By using autologous cells, there was no risk of immune activation and no immunosuppression was needed. COMET, however, might be associated with increased risk of persistent epithelial defects and graft failure, compared with allogenic CLET.